2010
DOI: 10.1351/pac-con-09-02-06
|View full text |Cite
|
Sign up to set email alerts
|

Auxin-producing Bacillus sp.: Auxin quantification and effect on the growth of Solanum tuberosum

Abstract: Plant-associated bacteria are known to improve plant growth and play a major role in the development of plants. The present study is concerned with the isolation of two auxin-producing plant growth-promoting bacteria (PGPB). On the basis of 16S rRNA sequencing, both of the strains are identified as Bacillus sp. Maximum auxin production was observed at 37 °C after 48 h of incubation. Increase in tryptophan concentration stimulated auxin production by the isolates. High-performance liquid chromatography analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(38 citation statements)
references
References 1 publication
0
29
1
Order By: Relevance
“…For instance, IAA producing B. flexus P4 and Bacillus sp. S6 increased Solanum tuberosum root length by 40 and 50%, respectively, compared with non-inoculated control 62 , while S. meliloti TSA41 and Streptomyces sp. W43N highly improved the levels of IAA in Dark Opal basil plants, in comparison with controls 63 .…”
Section: Discussionmentioning
confidence: 90%
“…For instance, IAA producing B. flexus P4 and Bacillus sp. S6 increased Solanum tuberosum root length by 40 and 50%, respectively, compared with non-inoculated control 62 , while S. meliloti TSA41 and Streptomyces sp. W43N highly improved the levels of IAA in Dark Opal basil plants, in comparison with controls 63 .…”
Section: Discussionmentioning
confidence: 90%
“…Auxin is one of the crucial molecules, regulating most plant processes directly or indirectly [80] as was further proven when Ahmed and Hasnain [35] reported that auxin-producing Bacillus spp. inflicts a positive effect on Solanun tuberosum ’s growth.…”
Section: Role Of Plant Growth Promoting Rhizobacteria For Plant Grmentioning
confidence: 99%
“…This bacterial IAA changes the plant auxin pool to either optimal or supraoptimal levels and improves plant growth directly hence proved to be crucial for better development of plants (Iqbal, Wagi & Ahmed, 2017). Bacterial IAA has phytostimulatory impacts and improves plant growth by improving plant roots development and increasing the surface area to volume ratio of roots and consequently results in better uptake of water and nutrients (Ahmed & Hasnain, 2010). The current study deals with the study of various growth promoting attributes of plant growth-promoting rhizobacteria (PGPR) isolates and impacts of various factors i.e.…”
Section: Introductionmentioning
confidence: 99%